Implementation of TMS320f28335 DSP code based on SVPWM technique for driving VSI with induction motor - Enas D. Hassan; Khalid G. Mohammed; Inaam I. Ali (Institute of Advanced Engineering and Science, 2022)
The ability to control the speed of three-phase induction motors is a complex and arduous task using conventional control methods because the induction motor still inherits traditional design problems such as nonlinear and multivariate reactive dynamic behavior that leads to difficult design of the motor's mathematical model, and the strict overlap between decades of mathematical parameters. This causes more complex relationships with changing loads. This complexity results in unacceptable behavior of the system, and the difficulty of controlling its speed without affecting the torque, and thus the specific calculations of engine efficiency are almost low. Therefore, the current research provides the implementation of devices for the V/f control method that is fed via Inverter of the voltage source using the new generation of digital signal processor TMS320F28335 according to the theory of space vector pulse width modulation (SVPWM) for the application of motor control. The results obtained from practical experience show the possibility of obtaining a wide range of control and thus reduce the damage to the system in the event of the load thus ensuring the reliability of the proposed control scheme is built on DSP.